ELABORATION OF THE ULTRASOUND GAME IN ACTION (REMUNOM, 2025)
Nowadays in the teaching-learning process, in all the levels of educational system, teachers, frequently, are unable to work the interests of their students. The traditional methods of teaching are often less attractive for the students. In this work we will present the possibility to explore the ludicity analyzing the dynamics and the effects of educational games in the Physics teaching that abode the ultrasound. When developed for content learning, it has the potential to become an important learning tool, presenting great potential to arouse students' interest in content, mainly because they address these contents within a playful environment, conducive to better learning, very different from classrooms in schools, which are usually expository. As a result of this work, the game "Ultrasound in Action" is presented.